A systematic review of educational robotics studies for the period 2010-2021 - Gunes, Habibe; Kucuk, Sevda (Wiley, 2022)
The aim of this research is to systematically review the theses on educational robotics applications produced in Turkey between the years 2010-2021. The aim is to provide a broad perspective on current studies by revealing the existing situation in the literature. For this purpose, 124 postgraduate theses in the national thesis database were examined within the scope of the research. The theses were analysed using the content analysis method and the educational robotics publication classification form. According to the results of the research, most theses were carried out in 2019 and educational robotics was mostly studied in the master's theses. Experimental design with the quantitative method and the quasi-experimental pre-test post-test control group was widely used as research methods. Research in the theses was mostly conducted in secondary schools. The implementations lasted between 1 and 2 months (6-8 weeks). The size of the study groups were 31-100 and the sample selection was appropriate for its purpose. Lego sets and Arduino sets were used the most in information technologies and software and science courses. The proposals sections of the theses suggest that future research should carry out studies with longer-term implementations and larger sample groups. For practitioners, the theses suggest that robotics-based activities should be added to the curriculum in every age group. They emphasize the need for a STEM-based robotics course for teachers as an in-service training course and that it would be beneficial to have robotics workshops in schools. The results obtained from the study are discussed in detail. The video abstracts for this article are available at and .
Keywords: educational robotics; robotics; systematic review